PENGEMBANGAN MODUL PERAWATAN KESEHATAN MENTAL BERBASIS HOME CARE - -, Tati; Jubaedah, Yoyoh; Yusup, Ayu Khairunnissa (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2019)
Development of Mental Health Nursing Care Module with Home Care Based Abstract The purpose of this study was to produce a Home care Based Mental Health Nursing Care Module. The method used was Research and Development with the ADDIE approach. However, the research was only carried out until the development stage. Modules were designed using expert judgment validation by experts to assess the feasibility of the modules that have been designed. The aspects assessed in the validation are aspects of the feasibility of the content and feasibility of the module. The final result of the validation carried out by experts in the field of elderly services and experts in the field of modules/media is the Home care Mental Health Care Mentoring Module Based on Home care stated that it is very feasible to use or implement. Recommendations of this research are shown to assistants, expected to be used as learning materials and reference materials in the Home care mental health care mentoring process. For further researchers, it is expected that research can be continued at the implementation stage can be carried out on family members who are elderly assistants at home. Keywords: elderly, module, mentoring, mental health care Abstrak Tujuan dari penelitian ini yaitu untuk menghasilkan Modul Pendampingan Lanjut Usia Berbasis Home care dalam Perawatan Kesehatan Mental. Metode yang digunakan yaitu Research and Development dengan pendekatan ADDIE. Pengembangan modul dilakukan melalui validasi expert judgment oleh ahli untuk menilai kelayakan modul yang telah dirancang. Aspek yang dinilai dalam validasi adalah aspek kelayakan isi dan kelayakan modul. Hasil akhir dari validasi yang dilakukan oleh ahli di bidang pelayanan lansia dan ahli di bidang modul adalah Modul Pendampingan Lanjut Usia Berbasis Home care dalam Perawatan Kesehatan Mental dinyatakan sangat layak untuk digunakan atau diimplementasikan. Rekomendasi dari peneitian ini ditunjukkan bagi pendamping, diharapkan dapat digunakan sebagai bahan belajar dan bahan acuan dalam proses pendampingan lanjut usia berbasis Home care dalam perawatan kesehatan mental. Bagi peneliti selanjutnya, diharapkan penelitian dapat dilanjutkan pada tahap implementasi dapat dilakukan pada anggota keluarga yang menjadi pendamping lanjut usia di rumah Kata Kunci: Modul, Pendampingan, Lanjut Usia, Perawatan Kesehatan Mental